Implementing Kahoot! for Japanese Language Learning in Indonesian High School - Adnyani, Kadek Eva Krishna; Adnyana, I Wayan; Murniasih, Ni Nyoman; Suwastini, Ni Komang Arie (Journal of Education Technology, 2022)
Kahoot! is an individual and collaborative gamified learning platform that encourages curiosity, promotes lifelong learning, and makes learning enjoyable. Given the numerous advantages of using Kahoot! in language acquisition, several academic institutions have included gamification to enhance their learning experience. However, there are always issues and hurdles encountered throughout technology deployment. The present study aimed to analyze how the teacher implements Kahoot! in Japanese learning, the Indonesian high school teachers and students' perceptions of using Kahoot! and the constraints they encountered in using Kahoot! The study was designed as qualitative research, enrolling one Japanese language teacher and 34 students in a state senior high school. Semi-structured interviews, non-participatory observation, and a mixed questionnaire were used to collect data. Despite specific problems in the teacher's implementation of Kahoot!, the research indicated that both the teacher and the students had an "excellent" impression of the platform, with a poor internet connection being recognized as the biggest stumbling block to their utilizing Kahoot! efficiently. While Kahoot! may be a realistic alternative for inspiring high school students to learn Japanese, it requires a solid internet connection to guarantee that the learning process runs well.